CLINICAL-EPIDEMIOLOGICAL CHARACTERISTIC OF ECHINOCOCCOSIS IN ZAPOROZHYE REGION - E. V. Ryabokon; O. V. Zarudnaya; N. S. Ushenina (Zaporožskij Medicinskij Žurnal)
Relevance of an echinococcosis is caused by case rate body height, late diagnostics, augmentation of number of the complicated forms, growing number of patients with atypical localizations of echinococcosis cysts.